Effect of dosing regime on nitrification in a subsurface vertical flow treatment wetland system - Kantawanichkul S. (2017)
In this study, the effect of dosing regime on nitrification in a subsurface vertical flow treatment wetland system was investigated. The experimental unit was composed of four circular concrete tanks (1 m diameter and 80 cm deep), filled with gravel (1-2 cm) and planted with Cyperus alternifolius L. Synthetic wastewater with average chemical oxygen demand (COD) and ammonia nitrogen of 1,151 and 339 mg/L was fed into each tank. Different feeding and resting periods were applied: continuous flow (tank 1), 4 hrs on and 4 hrs off (tank 2), 1 hr on and 3 hrs off (tank 3) and 15 minutes on and 3 hrs 45 minutes off (tank 4). All four tanks were under the same hydraulic loading rate of 5 cm/day. After 165 days the reduction of total Kjeldahl nitrogen and ammonia nitrogen and the increase of nitrate nitrogen were greatest in tank 4, which had the shortest feeding period, while the continuous flow produced the lowest results. Effluent tanks 2 and 3 experienced similar levels of nitrification, both higher than that of tank 1. Thus supporting the idea that rapid dosing periods provide better aerobic conditions resulting in enhanced nitrification within the bed. Tank 4 had the highest removal rates for COD, and the continuous flow had the lowest. Tank 2 also exhibited a higher COD removal rate than tank 3, demonstrating that short dosing periods provide better within-bed oxidation and therefore offer higher removal efficiency. © IWA Publishing 2012.